Solvothermal synthesis of ZnMn2O4 as an anode material in lithium ion battery - Song, Min Seob; Cho, Yong Jae; Yoon, Dong Young; Nahm, Sahn; Oh, Si Hyung; Woo, Kyoungja; Ko, Jang Myoun; Cho, Won Il (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
In order to reduce the solvothermal reaction time to prepare a pure phase of ZnMn2O4 as an anode material for lithium ion batteries, we have investigated the effect of the mixing times as an important reaction factor. It is found that the mixing times of zinc nitrate play an important role in removing the ZnO impurity phase which diminishes its electrochemical performance. The in-situ and ex-situ X-ray diffraction (XRD) for the pure phase of ZnMn2O4 during the first discharge and charge process showed that the crystalline ZnMn2O4 was converted to amorphous phase through a series of conversion reactions and the study of magnetic property revealed the MnO phase existed in the 1st cycled crystalline ZnMn2O4 electrode. The pure ZnMn2O4 electrode showed initial discharge capacity of about 820 mAh g(-1) and 57% of initial capacity retention after 50 cycles at a rate of C/10. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: NEGATIVE-ELECTRODE MATERIALS; CO3O4; OXIDE; NANOPARTICLES; PRECURSOR; ZNCO2O4; SPINEL